2022
DOI: 10.1158/1078-0432.ccr-22-0390
|View full text |Cite
|
Sign up to set email alerts
|

Facts and Hopes on the Use of Artificial Intelligence for Predictive Immunotherapy Biomarkers in Cancer

Abstract: Immunotherapy by immune checkpoint inhibitors (ICI) has become a standard treatment strategy for many types of solid tumors. However, the majority of cancer patients will not respond and predicting response to this therapy is still a challenge. Artificial intelligence (AI) methods can extract meaningful information from complex data, such as image data. In clinical routine, radiology or histopathology images are ubiquitously available. AI has been used to predict the response to immunotherapy from radiology or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Initial studies demonstrated this predictability in lung cancer 3 , breast cancer 4 , and colorectal cancer 5 . Subsequently, several "pan-cancer" studies showed that DL-based prediction of biomarkers is feasible across the whole spectrum of human cancer [6][7][8][9][10] . However, these studies were overwhelmingly performed in a single large cohort without externally validating the results on a large scale.…”
mentioning
confidence: 99%
“…Initial studies demonstrated this predictability in lung cancer 3 , breast cancer 4 , and colorectal cancer 5 . Subsequently, several "pan-cancer" studies showed that DL-based prediction of biomarkers is feasible across the whole spectrum of human cancer [6][7][8][9][10] . However, these studies were overwhelmingly performed in a single large cohort without externally validating the results on a large scale.…”
mentioning
confidence: 99%
“…The current clinical gold standard is PD-L1 staining of tumor tissue, but it is poorly predictive of patients who will respond to immunotherapy, nor those who will have adverse events due to the immune checkpoint inhibition (39). AI approaches to predict these by analyzing histopathology and radiological images have been published, but most employ DL learning approaches and interpretability/explainability is still a key issue (40). As in our discussion of melanoma prognosis, we believe that deep-learning and more interpretable approaches are both needed for effective clinical translation.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, in the 2010s, "Radiomics" machine-learning methods have used sets of expert-defined visual "features", coupled with simple ML models (Aerts et al 2014). More recently, end-to-end Deep Learning has been increasingly applied to such tasks (Ghaffari Laleh et al 2022).For example, AI has been used to prognosticate the course of colorectal cancer from digitized histopathology image data (Skrede et al 2020), or to predict the response to immunotherapy from radiological imaging data (Trebeschi et al 2019;Wu et al 2019;Ligero et al 2021). Also, AI has been used to predict the presence of genetic alterations from image data (Shmatko et al 2022;Kockwelp, et al 2022;Kather et al 2020), and is being discussed as a potential way to prescreen patients for targeted molecular testing (Shmatko et al 2022).…”
Section: Image Analysis Systemsmentioning
confidence: 99%